2017
DOI: 10.1371/journal.pone.0175795
|View full text |Cite
|
Sign up to set email alerts
|

The plant defense and pathogen counterdefense mediated by Hevea brasiliensis serine protease HbSPA and Phytophthora palmivora extracellular protease inhibitor PpEPI10

Abstract: Rubber tree (Hevea brasiliensis Muell. Arg) is an important economic crop in Thailand. Leaf fall and black stripe diseases caused by the aggressive oomycete pathogen Phytophthora palmivora, cause deleterious damage on rubber tree growth leading to decrease of latex production. To gain insights into the molecular function of H. brasiliensis subtilisin-like serine proteases, the HbSPA, HbSPB, and HbSPC genes were transiently expressed in Nicotiana benthamiana via agroinfiltration. A functional protease encoded b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…The recent semi-quantitative RT-PCR study showed that a protease inhibitor PpEPI10 gene was significantly up regulated during colonization of rubber tree by Phytophthora palmivora which later interact with the subtilisin proteases in rubber tree. This research revealed the strength of semiquantitative RT-PCR [32]. In this study, the semi-quantitative RT-PCR on HbPI transcripts was able to confirm the relatively stable expression among five conditions in rubber tree clone PB 260.…”
Section: Semi-quantitative Rt-pcrsupporting
confidence: 53%
“…The recent semi-quantitative RT-PCR study showed that a protease inhibitor PpEPI10 gene was significantly up regulated during colonization of rubber tree by Phytophthora palmivora which later interact with the subtilisin proteases in rubber tree. This research revealed the strength of semiquantitative RT-PCR [32]. In this study, the semi-quantitative RT-PCR on HbPI transcripts was able to confirm the relatively stable expression among five conditions in rubber tree clone PB 260.…”
Section: Semi-quantitative Rt-pcrsupporting
confidence: 53%
“…Another oomycete pathogen, Ph . palmivora also produced a KPI, PpEP to suppress plant defense [47]. Therefore, we speculate that the large number of KPIs secreted by P .…”
Section: Discussionmentioning
confidence: 99%
“…A degree of host specificity in the protease inhibitor suite may also occur in P. palmivora . This brutal pathogen is not deterred by the high levels of papain in papaya due to the efficiency of one of its cysteine protease inhibitors PpaEPIC8 (Gumtow et al ., 2018) whereas, for its infection of rubber trees, the Kazal‐like serine protease inhibitor PpEPI10 may be more important (Ekchaweng et al ., 2017).…”
Section: Pathogenicity Factors Enable Infectionmentioning
confidence: 99%